Through gusset connection for two-story X-braced frames, a numerical study. (October 2020) - Roostaeyan, Elahe; Rasoul Mirghaderi, Seyed; Ghazizadeh, Sina; Zahrai, Seyed Mehdi
Abstract: A common and efficient type of concentrically braced frames in practice is the two-story X-braced (split-X) system. Most of the studies conducted on this bracing configuration, investigated the inelastic response of the frame under dynamic loading. While the mid-span gusset connection affects the frame response considerably, a limited number of studies have focused on this type of connection. In this paper, a finite element analysis model is developed for mid-span gusset connections. The model is first validated with experimental results obtained from a two-story X-braced frame tested under quasi-static cyclic loading in the literature. Next, the model is used to investigate the response of a mid-span, through gusset connection, which consists of a double channel beam and a through plate. Case study results show that the brace-intersected beam experiences about 37% lower stresses in the proposed frame compared to the conventional frame. The proposed connection is shown to achieve higher strength and better integrity than the conventional system. Parametric analyses are also conducted to address the shear demands and some geometrical design aspects in both proposed and conventional systems.